Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12885-018-4183-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trastuzumab (Herceptin®) treatment in a continuation study of patients with HER2-positive breast cancer or HER2-positive gastric cancer

Abstract: BackgroundTrastuzumab (Herceptin® [H]) is the standard of care for HER2-positive locally advanced/metastatic breast cancer and gastric/gastroesophageal junction (GEJ) cancer. However, there is a paucity of data available on long-term H treatment of patients. The Rollover Protocol (ROP) Study was conducted to report safety data for patients with HER2-positive locally advanced/metastatic breast and gastric/GEJ cancer who have received long-term H therapy (≥ 5 years and ≥ 3 years for breast and gastric/GEJ cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
0
16
0
2
Order By: Relevance
“…Anti-HER-2 treatment is approved long-term for breast cancer, stomach cancer, and gastroesophageal junction cancer with HER-2 overexpression/amplification. (22)(23)(24) Several anti-HER2 clinical trials and case reports show that HER2 is a promising target in BTC, but anti-HER2 agents are still not approved for routine administration in BTC. (25) EGFR alterations were identified in 2.7% (5 of 186) of our cases.…”
mentioning
confidence: 99%
“…Anti-HER-2 treatment is approved long-term for breast cancer, stomach cancer, and gastroesophageal junction cancer with HER-2 overexpression/amplification. (22)(23)(24) Several anti-HER2 clinical trials and case reports show that HER2 is a promising target in BTC, but anti-HER2 agents are still not approved for routine administration in BTC. (25) EGFR alterations were identified in 2.7% (5 of 186) of our cases.…”
mentioning
confidence: 99%
“…One crucial purpose of molecular diagnosis in patients with cancer is to determine sensitive drug targets (34), including HER2, which could be specifically bound by herceptin, which is a monoclonal antibody used in anticancer therapy (35). The present study identified two true-positive HER2 CNV in patients.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, these studies showed that Trastuzumab was effective when used in monotherapy as well as in combination with platinum compounds (Baselga et al, 1996 ; Pegram et al, 1998 ). The effectiveness and safety of Trastuzumab have made it the gold standard treatment for women with metastatic breast cancer, alone or in combination with paclitaxel or doxorubicin, and for patients affected by HER2-positive metastatic gastric carcinoma (Müller et al, 2018 ). Finally, in 2013 a conjugated monoclonal antibody was approved, named Trastuzumab-emtansine.…”
Section: The Revolution Of Targeted Therapy: Selective Kinase Inhibitmentioning
confidence: 99%